Factors Associated with the Second Dose of Measles Immunization in Children Under Two Years: An ecological Study - Yenny Wulandari; Hario Megatsari; Agung Dwi Laksono; Mursyidul Ibad (Indian Journal of Forensic Medicine & Toxicology, 2021)
Measles is one of the leading causes of morbidity, mortality, and disability in children under two years worldwide. The study aimed to analyze factorsassociatedwiththe second dose of measles immunization in children under two years in 2019 in Indonesia. The study carried out the ecological analysis using secondary data from the 2019 Indonesian Health Profile. The Ministry of Health of the Republic of Indonesia reported that in 2019. The study takes 34 provinces as samples. The dependent variable is the coverage of the second dose of measles immunization in children under two years. The independent variable isthe ratio of primary health centers per district by province, the percentage of primary health centers with sufficient nurses, and the percentage of primary health centers with enough midwives. The results showed that three variables tended to be related to the second dose of measles immunization in childrenunder two years. The three variables consist of theratio of primary health centerper district, percentage of the primary health center with sufficient nurses, and percentage of the primary health center with enough midwives. The study concluded that the three independent variables analyzed tended to correlate with the coverage of the second dose of measles immunization in children under two years.